Modello altimetrico di precisione a basso costo su un’area di ampie dimensioni - Gatti, Marco; Casetto, Alessio (GEOmedia, 2010)
Low cost precise DTM on a wide area The paper describes the realization of a DTM on an area having extension of approximately 100.000 hectares. The model has been obtained from the interpolation of approximately 131.000 geodetic heights inside of 180 tablets of the Regional Technical Cartographic of the Emilia Romagna, to the nominal scale 1:5000. In order to improve its accuracy, approximately 1.550 benchmarks have been surveyed. The survey has been executed with VRS GPS technique. On the base of the benchmark geodetic heights a calibration of DTM heights has been executed, obtaining a new DTM. The new DTM has been verified and it has denounced differences in height less to the 30 cm. In the article we describe also the realization costs.